THE EFFECT OF INTERNAL CONTROL SYSTEMS, INTERNAL AUDITS, AND GOOD CORPORATE GOVERNANCE ON FRAUD PREVENTION IN ISLAMIC COMMERCIAL BANKS IN INDONESIA - Dewi Ayu Fatimatuz Zahro; Iwan Fakhruddin; Azmi Fitriati; Rina Mudjiyanti (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the influence of the internal control system, internal audit, and Good Corporate Governance on fraud prevention in Sharia Commercial Banks in Indonesia for the 2018–2024 period with company size as a control variable. Fraud prevention is measured using the anti-fraud strategy disclosure index based on content analysis of the annual report and the Good Corporate Governance report. This study uses a quantitative approach with unbalanced panel data consisting of 121 year-long bank observations from 20 Islamic Commercial Banks. The sample was determined using population-based selection with exclusion criteria. Data analysis was carried out using the Fixed Effect Model with the estimation of Driscoll–Kraay standard errors. The results of the study show that the internal control system and Good Corporate Governance have a positive and significant effect on fraud prevention, while internal audit and company size have no significant effect. These findings show that the effectiveness of fraud prevention is more determined by the quality of the implementation of the internal control system and Good Corporate Governance than the formal existence of internal audit functions and company size. The results of this study are expected to be input for regulators and management of Sharia Commercial Banks in strengthening control and governance mechanisms to increase the effectiveness of fraud prevention.